Intra-artiocular lipoma causing snapping in the patellofemoral joint - Yilmaz, Erhan; Karakurt, Lokman; Yidirim, Hanifi; Ozercan, Resat (Saudi Med J, 2007)
Intra-articular lipoma is an exceedingly rare diagnosis. We identified a lipoma that was seated in the retropatellar area and caused snapping of the patella during flexion of the knee joint. The tumor was easily and totally excised under arthroscopic guidance after the thin pedicle was cut.
Keywords: Intraarticular Lipoma; Knee-Joint; Arborescens; Locking